DIGITALISASI DAN AKSESIBILITAS PELAYANAN PUBLIK: STUDI PELAYANAN KEIMIGRASIAN BERBASIS E-GOVERNMENT - Januar Dwiky Rezaldi; Hanifa Maulidia; Seno Setyo Pujonggo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In the digital era, the use of technology in public services has become a pressing necessity, including in immigration services. This study aims to analyze the implementation of e-Government in the digitalization and accessibility of immigration services, particularly through the M-Paspor application. A descriptive qualitative approach was employed, with data collected through literature review and documentation. The results show that digitalization in immigration services has had a positive impact in terms of efficiency, transparency, and service quality improvement. Service access has become more widespread, although challenges such as low digital literacy and limited infrastructure in remote areas remain. Public perception of digital services is generally positive, especially regarding convenience and speed, though some groups still face technical difficulties. This study highlights the importance of improving digital literacy and strengthening infrastructure as key to successful e-Government implementation in the immigration sector.